Tathbiqu Kitabi Yassarna li Tanmiyati Maharati al-qira’ah Linnushusi al-arobiyai fi Ta’limi Lughati al-arobiyah - AlGhifari, Husain; Qomariyah, Lailatul (Qismul Arab: Journal of Arabic Education, 2024)
The learning process of teaching Arabic requires the right methods to make the learning process easier, more dancing, and more fun for students to achieve the desired learning goals. This study aims to: 1) learn about the use of the book of Yassarna in improving Arabic reading skills in the learning of Arabic in the As-Salafiyah alhamidiyah cottage. 2) Learn the ability of students to read Arabic texts in the teaching of the Arabic language in the As-Salafiyah alhamidiyah cottage. 3) Learn of the supportive and inhibitory factors of using the Book of Yassarna in enhancing Arabic text skills in Arabic learning in As-Salafiyah alhamidiyah cottage. The research uses qualitative methods with descriptive approaches and data collection techniques such as observations, interviews, and documentation. As for the results of the research, (1) the use of the book of Yassarna in developing Arabic text reading skills in the teaching of Arabic in the As-Salafiyah alhamidiyah cottage using fun and interesting material. (2) The process of teaching a pleasant book, understanding by arranging the material according to the chapter, then there will be a test reading the book of Yassarna, repeating if there are errors. (3) There are inhibitory and supportive factors. Some of these factors are from the environment around students, such as teachers, media, methods, and infrastructure. Potential teachers should teach the Yassarna book to new students so that future teachers can master both the material and the methods. Aim for learning to be achieved well.